Desain Front End Aplikasi Toko Sepatu Dixstore10 Menggunakan Metode Design Thinking - Wahyu Aziz Ramadhani; Bayu Priyatna; Elfina Novalia (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The objective of this study is to formulate the design of Dixstore10's front-end application interface by applying the design thinking method, which focuses on user needs. Dixstore10 is a local shoe store that supports local products and offers quality shoes to different groups. In this study, the design thinking approach is implemented in five main steps, which form the core of this method. In the "Empathize" phase, surveys and interviews are conducted to further understand user needs. In the next phase, "Define," the main problems to be solved are clearly formulated. This process develops user goals, which form the basis for developing the design structure. "Ideate" visualizes the initial concept through a sitemap, while "Prototype" represents the solution design using HTML, CSS, and JavaScript technologies. The tests were conducted using the System Usability Scale (SUS) method and yielded an average score of 80.3, indicating positive user acceptance of the designed interface. The results of this study not only make an important contribution to the development of the Dixstore10 application, but also serve as a reference for other MSMEs in designing user-centric digital platforms. The iterative approach ensures relevant and functional solutions to support the growth of the MSME sector.